Study of Inner Leaf Juice of Aloe Barbadensis in Restoring The Integrity Of Hepatocytes Against Experimentally Induced Liver Insult And Liver Fibrosis - Rodda, Raghuveer; Gera, Jemimah; Pande, Meenu; Chidrawar, Dr.Vijay R; Rao, Dr. V Uma Maheswara (Asian Journal of Pharmaceutical Research and Development, 2014)
Hepatocytes are the predominant liver cells which are responsible for the multifold functions of the liver and are susceptible to injury by the drugs like paracetamol. Herbal drugs play an important role in the cure of liver diseases. Aloe vera (Aloe barbadensis) has been used for many centuries for it’s curative and therapeutic properties, and health benefits associated have been attributed to the polysaccharides contained in the gel of the leaves. The purpose of present study was to evaluate the hepatocurative effect of aqueous extracts of polysaccharide fractions of Aloe barbadensis against paracetamol induced liver injury and to find out the dose of the fraction at which maximum restoration of integrity of hepatocytes occur. Polysaccharide fractions were identified and isolated by mass spectrometry and column chromatography, respectively. Hepatotoxicity was induced with a single dose of paracetamol 3 g/kg, orally. N-acetylcysteine was used as a standard drug. The hepatocurative effect of the fractions was studied by biochemical parameters like SGPT, MDA, GSH, bilirubin and albumin. Animals were divided into seven groups. The first three groups received normal, disease control and standard respectively. Fraction I was given at doses of 250 mg/kg and 500 mg/kg, orally to group four and five respectively. They did not show any significant effect in restoring the liver enzymes. Fraction II was given at doses of 250 mg/kg and 500 mg/kg, orally to last two groups respectively. All the animals were treated for seven days. Treatment with fraction II at a dose of 500mg/kg significantly (P<0.001) restored the levels of SGPT, MDA, GSH, bilirubin and albumin and showed that the fraction had maximum hepatocurative activity.